Economic growth and productivity: Italy and the role of knowledge - Ignazio Visco (PSL Quarterly Review, 2020)
The COVID-19 crisis has hit Italy severely: by mid-2020, GDP had returned to the level observed in 1993. This is the result not only of its sharp collapse in the first half of 2020, but also of its weak growth since the 1990s. Addressing the problems that have restrained the economy for 30 years is, therefore, as important as tackling those created by the pandemic. In Italy, to return to a path of sustainable growth, implementing reforms aimed at creating a business-friendly environment is necessary but not sufficient. When a country approaches the technological frontier, growth depends on the capacity to incorporate and foster innovation and on the quantity and quality of investment in education. and knowledge. After documenting Italy's delays in innovation and education, we discuss their interrelation with the structure of the productive system and argue that achieving higher growth rates require a technological and cultural transformation.
Keywords: E00; O30; I20; 330; Italy; stagnation; innovation; human capital